2008
DOI: 10.1111/j.1365-2648.2007.04489.x
|View full text |Cite
|
Sign up to set email alerts
|

Theory‐guided interventions for adaptation to heart failure

Abstract: Title.  Theory‐guided interventions for adaptation to heart failure Aim.  This paper is a report of a study to examine the effects of a Roy Adaptation Model‐based experimental education, exercise and social support programme on adaptation in persons with heart failure. Background.  In the past 20 years, a large number of studies have evaluated heart failure. Several studies of other chronic diseases have been based on the Roy Adaptation Model and show that this approach is useful in promoting adaptation for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 55 publications
3
34
0
6
Order By: Relevance
“…Also, other authors [7][8][9][10] confirm the relevance and effectiveness of the model based on Roy's assumptions in the care and education of the chronically ill patient chronically. Therefore, Roy adaptation model is used around the world, both in research aimed at the development of nursing, as well as in everyday nursing practice [11].…”
Section: Discussionmentioning
confidence: 65%
“…Also, other authors [7][8][9][10] confirm the relevance and effectiveness of the model based on Roy's assumptions in the care and education of the chronically ill patient chronically. Therefore, Roy adaptation model is used around the world, both in research aimed at the development of nursing, as well as in everyday nursing practice [11].…”
Section: Discussionmentioning
confidence: 65%
“…Finally, detailed training and care programs will be developed for resolving the problems (14). The findings of another study suggested that the Roy adaptation model could be used as a guideline for investigation of adaptation processes (17). A study conducted by Khalilzadeh et al showed that adaptation of patients to heart failure is at a poor level because of their lack of awareness about the nature of this disease, treatment methods, treatment regimens, and problems of this disease (16).…”
Section: Introductionmentioning
confidence: 99%
“…Residual stimuli relate to individual's personal traits, experiences, and beliefs and their effects on the immediate situation are not obvious 9 . Previous studies have shown the effectiveness of the RAM in promoting clients' adaptation [10][11][12][13] . However, to the best of our knowledge, only a few studies have investigated the effects of the RAM on women's adaptation to pregnancyrelated problems, particularly problems with selfconcept.…”
Section: Introductionmentioning
confidence: 99%